The Clinical Significance of the Impact of Vaping on Plasma Clozapine Levels - Harry, Nkechinyere Mary; Folorunsho, Ibrahim L.; Anona, Kenechukwu; Okafor, Nnenna; Anugwom, Gibson O. (Disease and Health Research: New Insights Vol. 4, 2024)
Background: Clozapine is an antipsychotic medication essential for treating treatment-resistant schizophrenia. Heinz Baumann and his team at Wander AG, a Swiss pharmaceutical company, first synthesized Clozapine in 1958. Its plasma levels are influenced by cytochrome P450 (CYP450) enzymes, particularly CYP1A2. Vaping and traditional smoking may impact clozapine metabolism. Objective: This study aims to explore how vaping affects the plasma levels of clozapine, focusing on the pharmacokinetic interactions between clozapine and vaping constituents, and the implications for clinical practice. Methods: A literature review was conducted to examine the interactions between nicotine smoking, CYP450 enzymes, and clozapine metabolism. Additionally, case reports were analyzed to understand the clinical implications for patients on clozapine who switch from smoking to vaping. Results: Unlike traditional smoking, vaping often lacks combustion products like polycyclic aromatic hydrocarbons (PAHs), leading to reduced CYP1A2 induction. Case reports showed that switching from smoking to vaping often results in elevated plasma clozapine levels due to decreased CYP1A2 activity, causing adverse effects from toxicity. However, some vape products containing combustible products like aldehydes and carbonyls can induce CYP450 enzymes, leading to subtherapeutic plasma clozapine levels. Conclusion: Switching from smoking to vaping may affect clozapine metabolism primarily through reduced activity of the CYP1A2 enzyme. This can lead to higher serum clozapine levels, hence increased risk of toxicity and deleterious adverse effects. But vaping can also lead to the induction of CYP450 enzymes thereby causing decreased plasma clozapine levels. So, the effect of vaping on plasma clozapine levels can be dependent on its constituent ingredients. Therefore, health professionals should carefully monitor plasma clozapine levels in patients who switch from smoking to vaping and adjust dosages as needed to maintain therapeutic efficacy and minimize adverse effects.